IMPROVING STUDENTS’ INDIRECT SPEECH PRACTICE IN WRITING THROUGH PICTURES OF LOCAL STORY NARRATIVE TEXT (English Education Journal, 2014)
Having realized the importance of English as one of the international languages, the students should master English writing skill as a means to deliver and share information, feeling, and thought in the globalization era. To produce a good writing, many language aspects should be paid attention well. Grammar is one of them. In the process of writing, students often fail to apply their knowledge of grammar. The condition is understood since in changing direct speech into indirect speech involves many types of grammar text and the changing of elements such as pronouns, verbs, and adverbs from the quoted speech sentences. This study aims to improve students’ indirect speech practice in writing through pictures of local story narrative text. An action research was carried out at twelfth graders of science program in SMA Negeri 1 Pabelan Semarang regency. The procedures included planning, implementing, observing, and reflecting. The result showed that the great improvement occurred. Students were enthusiastic to involve in the teaching learning process. The great students’ improvements were obtained when the students were successful in changing direct speech into indirect speech. Therefore, the use of pictures of local story narrative text is able to improve the students’ indirect speech practice.